Finding new purpose for vacancies in rural areas: a taxonomy of coworking space business models - Nina Thornton; Martin Engert; Andreas Hein; Helmut Krcmar (International Entrepreneurship and Management Journal, 2023)
As a result of the rural exodus over the last decades, unused vacancies in rural areas are at risk of falling into disrepair. Given the current trends of flexible workplaces and people returning to rural areas, their repurposing as coworking spaces (CWSs) by entrepreneurs poses a potential for sustainable future-oriented workplace solutions. However, there is little to no guidance on the structural configuration and business models of CWSs in rural areas available for these entrepreneurs. We apply a structured empirical research approach to create a comprehensive and specialized taxonomy, including a literature review and eleven interviews with operators of rural CWSs in Germany. The resulting taxonomy of business models of CWSs in rural areas based on an extension of the business model canvas contributes to the knowledge base on rural CWSs. We evaluate its usability through a case study and an entrepreneurial operator of a rural CWS, underlining its entrepreneurial and practice-oriented purpose. The study addresses several urgent topics, such as the future of work and new work (places), which enable and accelerate the development of CWSs outside agglomerations consequential to the COVID-19 pandemic. It also promotes social and sustainable entrepreneurship and the revitalizing, enhancing, and increasing of digital accessibility of rural regions.
Keywords: 650; Coworking Space; Rural Area; Business Model; Business Model Canvas; Entrepreneurship